Correlation among mutans streptococci counts, dental caries, and IgA to Streptococcus mutans in saliva - Koga-Ito, Cristiane Yumi; Martins, Clélia Aparecida Paiva de; Balducci, Ivan; Jorge, Antonio Olavo Cardoso [UNESP] (FapUNIFESP (SciELO), 2004)
Two-hundred and forty individuals were studied, divided into five groups as follows: caries-free children, children with caries, children with rampant caries, young adults with and without caries. Whole stimulated saliva was collected and all individuals were investigated for DMFT/dmft according to the WHO criteria and the simplified oral hygiene index (OHI-S). Quantitative analysis of the total aerobic flora and mutans streptococci in saliva was performed. Also, the level of salivary anti-S. mutans IgA was determined by ELISA. Children with rampant caries showed the highest OHI-S value. The highest total counts of microorganisms were found in the group of children with caries. No statistically significant differences were observed for salivary flow, OHI-S and microorganism counts between the groups of young adults. No correlation between mutans streptococci counts and anti-Streptococcus mutans IgA levels was observed in the studied groups. A correlation between increased anti-Streptococcus mutans IgA levels and caries-free status was observed among young adults but not among children.
Keywords: secretory immunoglobulin; adolescent; adult; bacterial count; child; dental caries; enzyme linked immunosorbent assay; epidemiology; female; human; immunology; isolation and purification; male; microbiology; preschool child; saliva; Streptococcus mutans; Adolescent; Adult; Child; Child, Preschool; Colony Count, Microbial; Dental Caries; Enzyme-Linked Immunosorbent Assay; Epidemiologic Methods; Female; Humans; Immunoglobulin A, Secretory; Male; Saliva